2010
DOI: 10.1021/jf100173x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols and Antioxidant Activity of Calafate (Berberis microphylla) Fruits and Other Native Berries from Southern Chile

Abstract: Calafate ( Berberis microphylla ) is a native berry grown in the Patagonian area of Chile and Argentina. In the present study the phenolic composition and antioxidant activity of its fruits were studied and also compared with data obtained for other berry fruits from southern Chile including maqui ( Aristotelia chilensis ) and murtilla ( Ugni molinae ). Polyphenolic compounds in calafate fruit were essentially present in glycosylated form, 3-glucoside conjugates being the most abundant anthocyanins. The anthoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
244
3
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(273 citation statements)
references
References 29 publications
23
244
3
3
Order By: Relevance
“…In B. buxifolia fruits, the remarkable positive and significant correlation between anthocyanin accumulation and colour, and soluble solids and soluble solids/total titratable acidity ratio is consistent with this view (Table 2). The anthocyanin content found in B. buxifolia fruits at maturity (753 mg ×100 g (1 FW) was comparable with that obtained in earlier growing seasons (Arena & Curvetto 2008), and similar to that reported by Ruiz et al (2010) Note: AFFP, after the full flower phase; F, firmness; C, colour; SS, soluble solids; TTA, total titratable acidity; SS/TTA, soluble solids/total titratable acidity ratio. ANOVA F(P), F statistic and probability at P 00.05.…”
Section: Fruit Colour Evolution and Anthocyanin Contentsupporting
confidence: 67%
See 1 more Smart Citation
“…In B. buxifolia fruits, the remarkable positive and significant correlation between anthocyanin accumulation and colour, and soluble solids and soluble solids/total titratable acidity ratio is consistent with this view (Table 2). The anthocyanin content found in B. buxifolia fruits at maturity (753 mg ×100 g (1 FW) was comparable with that obtained in earlier growing seasons (Arena & Curvetto 2008), and similar to that reported by Ruiz et al (2010) Note: AFFP, after the full flower phase; F, firmness; C, colour; SS, soluble solids; TTA, total titratable acidity; SS/TTA, soluble solids/total titratable acidity ratio. ANOVA F(P), F statistic and probability at P 00.05.…”
Section: Fruit Colour Evolution and Anthocyanin Contentsupporting
confidence: 67%
“…The kinetic growth behaviour of the fruit and the evolution of chemical properties during the fruiting period and different growing seasons have been studied in this species (Arena & Curvetto 2008), and recent research on the Berberis genus has studied the phenol content in leaves (Koncic et al 2010), roots (Surveswaran et al 2007;Tomosaka et al 2008) and fruits (Ruiz et al 2010). The beneficial effect of B. buxifolia fruits on oxidative stress induced by chloramphenicol on human blood has also been reported (Albrecht et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recently Ruiz et al (2010) demonstrated that the content of flavonols and polyphenols in this fruit is approximately 32 ± 4mg of gallic acid/100g of the fruit. However, in order to identify and isolate these compounds it is necessary to consider many factors such as the murtilla type (Shene et al, 2009;Alfaro et al, 2013) and the extraction system applied and evaluate the solvent used, the temperature and time of extraction, the solid/liquid ratio, and the size of the particles (Cacace & Mazza, 2002Castañeda-Ovando et al, 2009;Pompeu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They are widely used for the production of jams, liqueurs, syrups, juices, marmalades, compotes, and chocolates among other products (Muñoz et al, 1986). Commercial murtilla production of fresh (Scheuermann et al, 2014) and processed products is currently established because the fruit is known for its sweet and floral aroma (Scheuermann et al, 2008) and its polyphenol content (Shene et al, 2009;Ruiz et al, 2010;Rubilar et al, 2011;Speisky et al, 2012;Alfaro et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This plant contains several sesquiterpenes of the drimane type. Leaves of Drimys winteri are used in Chilean folk medicine as analgesic and in anti-infl ammatory medications (Houghton and Manby, 1998;San Martin, 1983;Cotoras et al, 2001;Muñoz and Fajardo, 2005;Muñoz et al, 2001;Ruiz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%